What Drives Paternity Leave: Financial Incentives or Flexibility? - Lennart Ziegler; Omar Bamieh (Institute of Labor Economics (IZA), 2023)
Despite changing gender norms, few fathers decide to take parental leave after the birth of a child, and when they do, their leave spells are substantially shorter compared to mothers. This study examines how paternal leave-taking is affected by two key features of leave policies: flexibility in leave duration and financial incentives. To disentangle their impact, we exploit recent changes to the Austrian parental leave system, which initially offered flat monthly benefits for 36 months after childbirth. The first reform added considerably shorter leave options; the second reform introduced income-dependent benefits, increasing net income replacement rates to 80 percent. Using a regression discontinuity design based on eligibility cutoff dates, we find that both reforms had a strong impact on leave take-up of fathers. The availability of shorter leave options increased leave-taking by 23 percent, while the introduction of income-dependent benefits raised take-up by another 13 percent relative to pre-reform means. Despite these increases, the share of leave taken by fathers relative to mothers remained similar. Comparing the impact of the two reforms across different income groups, we conclude that higher flexibility is more effective than stronger financial compensation in raising the number of leave-taking fathers.
Keywords: J12; J13; J18; J22; I38; 330; parental leave; gender differences; childcare; financial incentives; labor supply; return to work